The linguistic roots of natural pedagogy - Mattos, Otávio; Hinzen, Wolfram (Frontiers in Psychology, 2015)
Natural pedagogy is a human-specific capacity that allows us to acquire cultural information from communication even before the emergence of the first words, encompassing three core elements: (i) a sensitivity to ostensive signals like eye contact that indicate to infants that they are being addressed through communication, (ii) a subsequent referential expectation (satisfied by the use of declarative gestures) and (iii) a biased interpretation of ostensive-referential communication as conveying relevant information about the referent's kind (Csibra & Gergely, 2011, 2009, 2006). Remarkably, the link between natural pedagogy and another human-specific capacity, namely language, has rarely been investigated in detail. We here argue that children’s production and comprehension of declarative gestures around 10 months of age are in fact expressions of an evolving faculty of language. Through both declarative gestures and ostensive signals, infants can assign the roles of 3rd , 2nd and 1st person, building the ‘deictic space’ that grounds both natural pedagogy and language use. Secondly, we argue that the emergence of two kinds of linguistic structures (i.e. proto-determiner phrases and proto-sentences) in the one-word period sheds light on the different kinds of information that children can acquire or convey at different stages of development (namely, generic knowledge about kinds and knowledge about particular events/actions/state of affairs, respectively). Furthermore, the development of nominal and temporal reference in speech allows children to cognize information in terms of spatial and temporal relations. In this way, natural pedagogy transpires as an inherent aspect of our faculty of language, rather than as an independent adaptation that pre-dates language in evolution or development (Csibra & Gergely, 2006). This hypothesis is further testable through predictions it makes on the different linguistic profiles of toddlers with developmental disorders.